Ciudad, movilidad espacial y sectores populares: una aproximación al Sistema Integrado de Transporte Metropolitano del Gran Posadas, Misiones, Argentina - Paiva, Hernán Ramón (2015)
From a descriptive ethnographic approach this paper analyzes how popular class experience daily the passenger transport system in the city of Posadas, Misiones. The reason that leads to reflect on this issue are the strategies of urban mobility with the popular sectors to access urban centrality according to their different needs: work, education, health, recreation. Also observe these processes in the context of increasing urban sprawl, the product of public policies and market mechanisms that drive dispossessed populations. Towns are segregated, limited to the enjoyment of urban centrality, social and economic opportunities associated with the location of the home or business. This includes the right to transport and mobility as one of the principles of the right to the city. Finally, a public transport but private ownership should ensure the connection between different urban populations makes based on a utilitarian logic (individualistic) without adequate control of state is observed, leaving the entire organization in the hands of companies.